2020
DOI: 10.1002/jcad.12298
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development in Social Justice: Analysis of American Counseling Association Conference Programming

Abstract: This study was designed as a content analysis of 2012–2017 American Counseling Association conference sessions to examine how social justice was presented. Four findings emerged from the qualitative content analysis: (a) rates of social justice sessions varied over time; (b) there were more multicultural sessions than social justice sessions; (c) populations that were addressed least often and most often were identified; and (d) there was a decline in the number of social justice content sessions. Implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…One common theme found across different definitions of social justice is a focus on society, systems, and organizations (Dollarhide et al., 2020; Sanabria & DeLorenzi, 2019). A focus on social systems may also make operationalizing social justice difficult, as social systems and organizational dynamics are influenced by a combination of factors, individuals, and groups (e.g., stakeholders; Kira et al., 2015).…”
Section: Social Justice Outcomes and Professional Counseling: An 11‐y...mentioning
confidence: 99%
See 1 more Smart Citation
“…One common theme found across different definitions of social justice is a focus on society, systems, and organizations (Dollarhide et al., 2020; Sanabria & DeLorenzi, 2019). A focus on social systems may also make operationalizing social justice difficult, as social systems and organizational dynamics are influenced by a combination of factors, individuals, and groups (e.g., stakeholders; Kira et al., 2015).…”
Section: Social Justice Outcomes and Professional Counseling: An 11‐y...mentioning
confidence: 99%
“…Articles from these JCD and JSGW special issues alone account for 37.1% of the entire dataset. Dollarhide et al (2020) posited that as a profession, counselors and counselor educators are more likely to react to current events when addressing social justice as opposed to proactively centering social justice in professional identity, social advocacy, and related scholarship. Analysis of the social justice counseling outcome research appears to show a similar reactivity, arising in response to current events such as the Coronavirus Disease 2019 (COVID-19) pandemic, the Black Lives Matter movement, and related demonstrations in the wake of increased anti-Black racism (Steen & Hines, 2020).…”
Section: Finding 4: Lack Of Evaluation Of Systemic Change Over Timementioning
confidence: 99%
“…Moreover, social justice content appears to be limited in other professional development opportunities such as conferences and peer reviewed journals. One content analysis of ACA annual conference offerings found that from 2012 to 2017, only an average of 3.75% of the conference sessions addressed social justice for multicultural groups or general social justice skills (Dollarhide et al., 2020). Another study found that African American male authors who wished to publish social justice content were rejected by counseling‐related peer reviewed journals (Dollarhide et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…If this individual-centric paradigm prevails, then the counselor may be perpetuating oppression through reliance on privileged values and worldviews (Crethar & Winterowd, 2012;Monk et al, 2008). This dynamic operates at organizational levels also (Dollarhide et al, 2014;Monk et al, 2008), suggesting that social justice must also be practiced at organizational levels to facilitate social justice at the individual level (Dollarhide et al, 2020). In response to concerns about the privilege-based lens of the counseling profession, the leaders of Counselors for Social Justice (CSJ) organized a Social Justice Summit (an ACA Presidential sponsored session) at the national conference for the American Counseling Association in New Orleans in March 2019.…”
mentioning
confidence: 99%
“…Concerning conference programming to give back to the community, discussants suggested it could be of advantage to create a distinctive social justice conference, where the current ACA day of service might be institutionalized and expanded to serve the host community that transcends the conference. Moreover, to raise awareness about social justice concerns, discussants urged ACA to advocate for specific conference breakout sessions to address clients' intersectionality of multiple identities and the study of social justice competency interventions (see Dollarhide et al, 2020).…”
mentioning
confidence: 99%